Mutações Kras e ativação da via de sinalização MAPK/ERK em lesões periféricas de células gigantes associadas ao implante dentário - Roberta Rayra Martins Chaves (2019)
Giant cell lesions (GLC) are a group of jaw diseases that share the same histopathological features. The GCL of the jaws have two distinct clinical subtypes: central and peripheral. The central giant cell lesion (CGCL) is an intraosseous disease, often asymptomatic that most commonly affects young individuals in the anterior region of the jaw. Peripheral giant cell lesion (PGCL) is clinically characterized by nodule with a reddish-purple color, mainly presented in the gingiva or alveolar mucosa of female individuals between the fourth and fifth decades of life. In some cases, PGCL may develop adjacent to a dental implant. The clinical and histopathological features of these lesions are very similar to those of non-implant-associated lesions. Recently, our research group reported recurrent, mutually exclusive and activating mutations in the TRPV4, KRAS and FGFR1 genes and a consequent constitutive activation of the MAPK/ERK intracellular signaling pathway in the GCL of the jaws. However, the molecular profile of PGCL associated with dental implants has not been determined. Thus, the objective of this study was to evaluate the molecular profile of the PGCL associated with dental implants by the investigation of KRAS, FGFR1 and TRPV4 mutations previously reported in the conventional lesions. MAPK activation was also evaluated through the immunohistochemical expression of the phosphorylated form of ERK1/2 proteins (phosphoERK1/2). For this purpose, 15 samples of PGCL associated with dental implant were used. Activating mutations in the KRAS gene were found in 7 of the 15 samples analyzed, affecting codons 12 (p.G12A / D), 14 (p.V14L), 37 (p.E37K) and 146 (p.A146V). Mutations in FGFR1 and TRPV4 genes were not detected. Mononuclear cells were strong staining by phospho-ERK1/2 protein in the immunohistochemical analysis, which confirmed the activation of the MAPK/ERK pathway in the PGCL associated with dental implants. In conclusion, the present study shows MAPK/ERK pathway activation in PGCL associated with dental implants. Our findings also demonstrate that the lesions associated with dental implants present a similar molecular profile with the conventional PGCL.